Analisis Minat Membaca Siswa Melalui Program Pojok Baca - Fauziah, Muna; Sari, Ela Yuniata (Paedagogie, 2025)
The purpose of this study was to analyze students' reading interest at MI Al Hidayah Karangtanjung. This study was a qualitative study. The roles of the school community studied consisted of the principal, class teachers, librarians, and students. The method used in this study was a case study method. Data collection techniques were in the form of observation results, interviews, documentation, and questionnaires. Data analysis techniques used were data condensation, data presentation, and drawing conclusions. The results showed that students' reading interest at MI Al Hidayah Karangtanjung in grades IV, V, and VI was included in the good category, marked by indicators of students' feelings of pleasure when reading, students' interest in reading, students' desire to find reading materials, and students' needs in reading. Students' reading interest has been optimized through the existence of a reading corner that functions by getting students used to reading for 15 minutes before learning and is supported by motivation by teachers. Thus, students at MI Al Hidayah Karangtanjung have shown a cultural interest in reading through the existence of a reading corner